Unmasking the impact of COVID-19 on the mental health of college students: a cross-sectional study - Gandhi, Subi; Jordan, Alexandra; Glaman, Ryan; Morrow, Brendan (Frontiers in Psychiatry, 2024)
Introduction: Safeguarding college students' mental health and well-being poses a challenge for college administrators and clinicians because of the unique circumstances students face and the limited literature on their needs. Prior to the pandemic, depression and anxiety were already on the rise among college students, but the changes associated with it may have exacerbated these issues. Our study aimed to explore factors influencing college students' mental health and identify common trends in their experiences that could assist organizations and policymakers in the future. Methods: The study participants (n = 571) were chosen using a convenience sample of undergraduate and graduate students attending a Central Texas university. We employed the Qualtrics survey platform to collect data on multiple demographic variables, behavioral health, and other health outcomes of students in the summer semester of 2021. Our objective in this study was to investigate the various factors that contribute to mental health conditions, particularly anxiety, and depression, independently and jointly, by employing two validated tools -Patient Health Questionnaire 9 (PHQ-9), which measures depression, and General Anxiety Disorder 7 (GAD-7), which measures anxiety. Results: Both the tools displayed satisfactory internal consistency, with Cronbach's alpha coefficients (𝛂) of 0.921 for the PHQ-9 (9-item) scale and 0.943 for the GAD-7 (7-item) scale. The prevalence of depression and anxiety among participants was 39.4% and 40.1%, respectively, with 31% of participants overall reporting both conditions. Among the explored factors, age, race, parent/guardian's level of education, campus residence status, and health insurance status were associated with depression (p < 0.05), whereas gender, age, race, and parent/guardian's level of education were associated with anxiety (p < 0.05). Academically, several factors related to learning difficulties (i.e., staying motivated to learn, finding a quiet place to learn) were associated with the severity of depression and anxiety severity, demonstrated through composite scores. Conclusion: Robust longitudinal studies should be carried out to ascertain key influencers that affect students' mental health, and colleges and universities should create policies and protocols to provide support for students during major catastrophes, such as the COVID-19 pandemic, taking into account these influencing factors.